Screening of brinjal (Solanum melongena) varieties/hybrids against two-spotted spider mite (Tetranychus urticae) - WALIA, GURPREET SINGH; BHULLAR, MANMEET BRAR; KAUR, PARAMJIT (The Indian Journal of Agricultural Sciences, 2014)
It can be summarised from these studies that brinjal varieties Punjab Sadabahar and Punjab Neelam were the most susceptible while hybrid BH 1 was relatively less preferred to two-spotted spider mite (Tetranychus urticae) attack. It indicated that variability exists in brinjal varieties/ hybrids and continuous screening of new genotypes is essential to find out tolerant genotypes which can fit in IPM programmes.